Psychometric Properties and Configural Invariance of the Polish – Language Version of the 20-Item Toronto Alexithymia Scale in Non-clinical and Alcohol Addict Persons - Ścigała, Dawid Konrad; Zdankiewicz-Ścigała, Elżbieta; Bedyńska, Sylwia; Kokoszka, Andrzej (Frontiers in Psychology, 2020)
Aim: The development and assessment of the psychometric properties of the Polish-language version of the Toronto Alexithymia Scale (Bagby et al., 1994 a, b) is described in this article. The aim of this study was to translate the TAS - 20 into Polish and establish the psychometric properties of this instrument evaluating alexithymia. Materials and Methods: Data were collected via self-report measures from a total sample of 676 participants: a total of 180 participants (115 males and 65 females) diagnosed with alcohol dependence, and 496 control group (347 males and 149 females). Results: Confirmatory factor analyses found the factor structure of the original English-language TAS 20 for the three subscales translated into Polish: Difficulty in Identifying Feeling (DIF); Difficulty in Describing Feeling (DDF); Externally Oriented Thinking (EOT). All three subscales showed good internal consistency in nonclinical group and two subscales, DIF and DDF in alcohol addict group. Several EOT items loaded poorly on their intended factor. Conclusion: The results from the present study indicate that the Polish version of the TAS - 20 is a reliable and valid measure of alexithymia with good levels of internal consistency, homogeneity, and construct validity. We conclude that the TAS-20 has, for the most part, adequate psychometric properties, though interpretation should focus only on the total scale score and DIF and DDF subscales, especially in clinical groups.